Sie sind auf Seite 1von 12

CHAPTER 103 EVEN AND ODD FUNCTIONS AND HALF-RANGE

FOURIER SERIES

EXERCISE 364 Page 1076

1. Determine the Fourier series for the function defined by:

 π
 − 1, − π 〈 x 〈 − 2

 π π
f(x) =  1, − 〈 x 〈
 2 2
 π
 − 1, 2 〈 x 〈 π

which is periodic outside of this range of period 2π.

The square wave shown is an even function since it is symmetrical about the f(x) axis.


Hence, the Fourier series is given by: f(x) = a 0 + ∑a
n =1
n cos nx

(i.e. the series contains no sine terms)

π {∫ }
1 π 1 π /2 π

π∫
a0 = f ( x) d x = 1d x + ∫ −1d x
0 0 π /2

=
1
π
{[ x] π /2
0
+ [ − x ] π /2 =
π
} π
1
[ (π) + [(– 2π) – (– π)] ] =0

an =
2
π ∫
π

0
f ( x) cos nx d x =
2
π {∫ π /2

0
1cos nx d x + ∫
π

π /2 }
−1cos nx d x

1526 © 2014, John Bird


π /2 π
2   sin nx   − sin nx  
=  + 
π   n  0  n  π /2 

2  sin(π / 2)n   − sin(π / 2)n  


=  − 0 + 0 − 
π  n   n 

2  2sin(π / 2)n  4  nπ 
=  =  sin 
π n  π n 2 

When n is even, a n = 0

4
When n is odd, a n = for n = 1, 5, 9,...
πn

−4
and an = for n = 3, 7, 11,...
πn

4 −4 4
Hence, a 1 = , a3 = , a5 = , and so on
π 3π 5π

Hence the Fourier series for the above waveform is given by:

4 1 1 1 
f(x) =  cos x − cos 3 x + cos 5 x − cos 7 x + ... 
π 3 5 7 

2. Obtain the Fourier series of the function defined by:

 t +π, −π 〈 t 〈 0
f(t) = 
 t −π, 0 〈 t 〈 π

which is periodic of period 2π. Sketch the given function.

The periodic function is shown in the diagram below. Since it is symmetrical about the origin, the

function is odd, and f (t ) = ∑ bn sin nt
n =1

1527 © 2014, John Bird


π {∫ }
1 π 1 0 π

π∫π
b=
n f (t ) sin nt d=
t (t + π ) sin nt d t + ∫ (t − π ) sin nt d t
− −π 0

π
1  t cos nt sin nt π cos nt   t cos nt sin nt π cos nt 
0

= − + − + − + + by integration by parts
π  n n2 n  −π  n n2 n  0

  π cos nπ π cos nπ  
   − + 0 +  
1   π   −π cos(−nπ ) π cos(−nπ )    n n   
=   0 + 0 −  −  − +0−  + 
π   n  n n   π 
 −  0 + 0 +  
   n   

1  π π cos(−nπ ) π cos(−nπ ) π cos nπ π cos nπ π  1  2π  2


= − − + − + −  = − =−
π n n n n n n π  n  n
2 2 2 2
Hence, b1 = − , b2 = − , b3 = − , b4 = − , and so on
1 2 3 4
2 2 2 2
i.e. f(t) = − sin t − sin 2t − sin 3t − sin 4t − ...
1 2 3 4
 1 1 1 
i.e. f (t ) =
−2  sin t + sin 2t + sin 3t + sin 4t + ... 
 2 3 4 

 1 − x, − π 〈 x 〈 0
3. Determine the Fourier series defined by f(x) =  which is periodic of period
 1 + x , 0 〈 x 〈 π
2π.

The periodic function is shown in the diagram below. Since it is symmetrical about the f(x) axis, the

function is even, and ) a0 + ∑ an cos nx
f ( x=
n =1

1 π 1 π
=a0 =
2π ∫ −π
f ( x) d x
π ∫ 0
f ( x) d x due to symmetry

π
1 π 1 x2  1  π2   π
= ∫ (1 + x) d x = x +  = π +  − ( 0 ) =
1+
π 0 π 2  0 π  2   2

π {∫ }
1 π 1 0 π

π∫π
a=
n f ( x) cos nx d=
x (1 − x) cos nx d x + ∫ (1 + x) cos nx d x
− −π 0

1528 © 2014, John Bird


π {∫ }
1 π
( cos nx − x cos nx ) d x + ∫0 ( cos nx + x cos nx ) d x
0
=
−π

0 π
1  sin nx x sin nx cos nx   sin nx x sin nx cos nx 
= − − + + + by integration by parts
π  n n n 2  −π  n n n 2  0

1   1   cos(−nπ )    cos nπ   1  
=   0 − 0 − 2  −  0 − 0 −  +
   + +  −  + +  
n 2   
0 0 0 0
π   n   n2    n2  

1  1 cos(−nπ ) cos nπ 1  2
= − 2 + + =−  ( cos nπ − 1) since cos(–nπ) = cos nπ
π n n2 n2 n2  π n2
When n is even, an = 0
2 4
When n = 1, a1 = ( −1 − 1) =−
π (1) 2 π
2 4
When n = 3, a3 = ( −1 − 1) =−
π (3) 2 π (3) 2
2 4
When n = 5, a5 = ( −1 − 1) =− and so on
π (5) 2 π (5) 2

π 4 4 4
) a0 + ∑ an cos nx =
f ( x= +1 − cos x − cos 3 x − cos 5 x − ...
n =1 2 π π (3) 2 π (5) 2
π 4 1 1 
i.e. f(x) = +1−  cos x + 2 cos 3 x + 2 cos 5 x + ... 
2 π 3 5 

4. In the Fourier series of Problem 3, let x = 0 and deduce a series for π2/8

When x = 0 in the series of Problem 3, f(x) = 1,

π 4 cos 0 cos 0 
hence, 1= +1−  cos 0 + 2 + 2 + ... 
2 π 3 5 
π 4 1 1 1 
i.e. 1= +1− 1 + 2 + 2 + 2 + ... 
2 π 3 5 7 
π 4 1 1 1 
i.e. − =− 1 + + + + ... 
2 π 3 5 7
2 2 2

π2 1 1 1
and =+
1 + + + ...
8 32 52 7 2

5. Show that the Fourier series for the triangular waveform shown is given by:

8  1 1 1 
y=  sin θ − sin 3θ + sin 5θ − sin 7θ + ... 
π2  32 52 72 
1529 © 2014, John Bird
The function is periodic of period 2π

The equation of the function between 0 and π/2 is of the straight line form y = mθ + c where
1 2
gradient, m = = and intercept, c = 0
π /2 π

Hence, equation of the line between 0 and π/2 is y =
π

The equation of the function between π/2 and 3π/2 is of the straight line form y = mθ + c where

2 2 2
gradient, m = = − When θ = π, and y = 0 and since y = mθ + c then 0 = − π+c
−π π π


from which, c = 2. Hence, equation of line between π/2 and 3π/2 is y = − +2
π

The equation of the function between 3π/2 and 2π is of the straight line form y = mθ + c where
1 2 2
gradient, m = = When θ = 2π, and y = 0 and since y = mθ + c then 0 = (2π) + c
π /2 π π

from which, c = –4. Hence, equation of line between 3π/2 and 2π is y = −4
π

The triangular wave is an odd function since it is symmetrical about the origin


Hence, the Fourier series is given by: f(θ) = ∑ ( b n sin nθ) i.e. a 0 = a n = 0
n =1

2 π 2  π /2 2θ π  2θ  
bn =
π ∫ 0
f ( x) sin nx d x =
π ∫ 0 π
sin nθ d θ + ∫ π /2 −
 π
+ 2  sin nθ d θ 
 

π /2 π π
2  2  θ cos nθ sin nθ  2  θ cos nθ sin nθ   2 cos nθ  
 − + − − + − 
π  π  n n 2  0 π n n 2  π /2  n  π /2 

1530 © 2014, John Bird


2  2  (π / 2) cos nπ / 2 sin nπ / 2  
=   − +  − ( 0 ) 
π  π  n n2  

2  2  (π ) cos nπ sin nπ   (π / 2) cos nπ / 2 sin nπ / 2   


 − + −− +  
π  π 

n n2   n n2  

2  2 cos nπ 2 cos nπ / 2 
– −
π  n n 

4  1  4 π 1  2  2 4 4 4 4 8
Thus, b 1 =  −0 +  −  + 0 −  −  −  = − + + =
π2  12  π 2  1 12  π  1  π 2 π π 2 π π 2

4 π  4  π π  2  2 2 1 3 4
− − − − + = + − =
π 2  4  π 2  2 4  π  2 2  π π π
b2 = 0 = b 4 = b 6 = b 8 , and so on

4  1  4 π 1  2  2 4 4 4 4 8
b3 = − 2 − 2  + 2 − −  = − 2 2 − − + =

π  3  π  3 3  π  3
2 π 3 3π π 2 32 3π π 2 32

4  1  4 π 1  2  2 4 4 4 4 8
b5 =  −0 + 2  − 2  + 0 − 2  −  −  = 2 2 − + + =
π 
2 5  π 5 5  π  5  π 5 5π π 2 52 5π π 2 52

8
It follows that b 7 = and so on
π 72
2


8 8 8 8
Thus, y= ∑b
n =1
n sin nθ =
π2
sin θ −
π 2 32
sin 3θ +
π 2 52
sin 5θ −
π 2 72
sin 7θ + ...

8  1 1 1 
i.e. y=  sin θ − sin 3θ + sin 5θ − sin 7θ + ... 
π2  32 52 72 

1531 © 2014, John Bird


EXERCISE 365 Page 1079

1. Determine the half-range sine series for the function defined by:

 π
 x, 0 〈 x 〈 2
f(x) = 
 0, π 〈 x 〈 π
 2

The periodic function is shown in the diagram below. Since a half-range sine series is required, the


function is symmetrical about the origin and f ( x) = ∑ bn sin nx
n =1

{ }
π /2
2 π 2 π /2 2  x cos nx sin nx 
bn =∫
π 0
f ( x) sin nx d x =∫ x sin nx d x =
π 0 π 

n
+
n 2  0
by integration by parts

 π nπ nπ  
cos sin
2  2  
 − ( 0 )
=  − 2 + 2
π  n n2  
  

 π π π 
  cos sin  2 
2 1 2
Hence, b1 =  − 2 2+ 2
 =  0 + 2  = ,
π  1 12
 π  1  π
  

 π 
cos π
2  2 sin π  2  π  2 π 
b2 =  − +  =  + 0 =  ,
π  2 22  π  4  π  4
  

 π 3π 3π 
cos sin
2  2 2 + 2  2  1 2
b3 = −  = 0− 2  =
− ,
π  3 32  π  3  π (3) 2
  

1532 © 2014, John Bird


 π 
cos 2π
2  2 sin 2π  2  π  2 π 
b4 =  − +  =  − + 0  =−  , and so on
π  4 42  π  8  π8
  

2 2 π  2 1  2 π 
Hence, f ( x) = ∑ bn sin nx = sin x +   sin 2 x −  2  sin 3x −   sin 4 x + ...
n =1 π π 4 π 3  π8
2 π 1 π 
i.e. f ( x) =  sin x + sin 2 x − sin 3 x − sin 4 x + ... 
π 4 9 8 

2. Obtain (a) the half-range cosine series and (b) the half-range sine series for the function

 π
 0, 0 〈 t 〈 2
f(t) = 
 1, π 〈 t 〈 π
 2

(a) The periodic function is shown in the diagram below. Since a half-range cosine series is


required, the function is symmetrical about the f(t) axis and ) a0 + ∑ an cos nt
f (t=
n =1

1 π 1 1 π 1
[t ] π /2 =
π

π ∫π
a0 = 1d t = π − =
/2 π π  2  2

 nπ  nπ
π sin 2sin
2 π 2  sin nt  2 
π ∫π /2
an = 1cos nt d t = = 2 2
0− =−
π  n  π /2 π  n  π n
 
When n is even, an = 0
π 3π 5π
2sin 2sin 2sin
2 =2 2
2 =  1  2 =2 1
and a1 =
− − , a3 =
−   , a5 =
− −   , and so on
π π 3π π 3 5π π 5


1 2 2 1 2 1
Thus, a0 + ∑ an cos nt =
f (t ) = − cos t +   cos 3t −   cos 5t + ...
n =1 2 π π 3 π 5

1533 © 2014, John Bird


1 2 1 1 
i.e. f (t ) =−  cos t − cos 3t + cos 5t − ... 
2 π 3 5 

(b) The periodic function is shown in the diagram below. Since a half-range sine series is required,


the function is symmetrical about the origin and f ( x) = ∑ bn sin nx
n =1

π
2 π 2  cos nt  2  nπ 
bn =∫
π π /2
1sin nt d t =
π 

n  π /2
=

nπ 
cos nπ − cos
2 

2 π 2 2
Hence, b1 =−  cos π − cos  =− ( −1 − 0 ) = ,
π 2 π π
2 2 2
b2 = − ( cos 2π − cos π ) = − (1 − −1) = − ,
2π 2π π
2  3π  2 2
b3 =−  cos 3π − cos  =− ( −1 − 0 ) = ,
3π  2  3π 3π
2 2
b4 =
− ( cos 4π − cos 2π ) =
− (0 − 0) =
0,
4π 4π
2  5π  2 2
b5 =−  cos 5π − cos  =− ( −1 − 0 ) = ,
5π  2  5π 5π
2 2 2
b6 = − ( cos 6π − cos 3π ) = − (1 − −1) = − , and so on
6π 6π 3π

2 2 2 2 2
Thus, f (t ) = ∑ bn sin nt = sin t − sin 2t + sin 3t + 0 + sin 5t − sin 6t + ...
n =1 π π 3π 5π 3π
2 1 1 1 
i.e. f (t ) =  sin t − sin 2t + sin 3t + sin 5t − sin 6t + ... 
π 3 5 3 

3. Find the half-range Fourier sine series for the function f(x) = sin2 x in the range 0 ≤ x ≤ π. Sketch

the function within and outside of the given range.

The periodic function is shown in the diagram below. Since a half-range sine series is required,

1534 © 2014, John Bird



the function is symmetrical about the origin and f ( x) = ∑ bn sin nx
n =1

2 π 2 2 π1 1 π
bn =∫
π 0
sin x sin nx d x =∫
π 0 2 π ∫0
(1 − cos 2 x) sin nx d x = (sin nx − cos 2 x sin nx) d x

2 π  1  
sin nx −  ( sin(2 + n) x − sin(2 − n) x )  d x 
π∫
=
0
 2  

π
1  − cos nx 1  − cos(2 + n) x cos(2 − n) x  
=  −  + 
π n 2  (2 + n) (2 − n)   0

1  − cos nπ cos(2 + n)π cos(2 − n)π   −1 1 1 


 + − − + − 
π  n 2(2 + n) 2(2 − n)   n 2(2 + n) 2(2 − n)  

Hence,
1 1 1 1 1  1 8 8
b1 = 1 − + +1− + =  =
π  2(3) 2(1) 2(3) 2(1)  π  3  3π

1 1 1 1 1 1 1 
b2 = − + − + − + = 0 = b4 = b6 = b8 and so on
π  2 2(4) 2(0) 2 2(4) 2(0) 

1 1 1 1 1 1 1  1  2 1  1  10 − 3 − 15  8
b3 =  − + + − +  =  − − 1 =   =−
π  3 2(5) 2(−1) 3 2(5) 2(−1)  π  3 5  π  (3)(5)  π (3)(5)

1 1 1 1 1 1 1  1  2 1 1  1  42 − 15 − 35  8
b5 =  − + + − + =  − − =  =−
π  5 2(7) 2(−3) 5 2(7) 2(−3)  π  5 7 3  π  (3)(5)(7)  π (3)(5)(7)
8
It follows that b7 = − and so on
π (5)(7)(9)

8 8 8 8
Thus, f ( x) = ∑ bn sin nx = sin x − sin 3 x − sin 5 x − sin 7 x
n =1 3π π (3)(5) π (3)(5)(7) π (5)(7)(9)

1535 © 2014, John Bird


8  sin x sin 3 x sin 5 x sin 7 x 
i.e. f ( x) =
sin 2 x =  − − − − ... 
π  (1)(3) (1)(3)(5) (3)(5)(7) (5)(7)(9) 

4. Determine the half-range Fourier cosine series in the range x = 0 to x = π for the function

defined by:

 π
 x, 0〈 x〈
f(x) =  2
(π − x), π 〈 x 〈 π
 2

The periodic function is shown in the diagram below. Since a half-range cosine series is required,


the function is symmetrical about the f(x) axis and ) a0 + ∑ an cos nx
f ( x=
n =1

{∫ }
π /2 π
1 π /2 π 1   x 2   x 2  
=a0 xd x + ∫ (π − x=
)d x  + π x − 
π 0 π /2 π   2  0  2  π /2 

1 π 2  2 π 2   π 2 π 2 
 + π − − − 
π  8 
=
2   2 8 

1  π 2 π 2 π 2 π 2  1  2π 2  π
+ − +=  =
π  8  
=
2 2 8  π 8  4

π {∫ }
2 π /2 π
=an x cos nx d x + ∫ (π − x) cos nx d x
0 π /2

π /2 π
2   x sin nx cos nx   π sin nπ x sin nx cos nx  
=  + + − − 
π   n n 2  0  n n n 2  π /2 

 π nπ nπ   nπ π nπ nπ 
2  2
sin cos   π sin sin cos  
2 + 2 1   cos nπ   2 − 2 2 − 2
=   −0 + 2  +0 −0 − − 
π  n n2   n   n2   n n n 2

    

1536 © 2014, John Bird


 nπ nπ nπ 
 2 cos π sin π sin
π  2  nπ
2 1 cos n 
=  2 + 2 − − 2=−  2 cos − 1 − cos nπ 
π n 2 n n 2 n n  πn 
2 2 2 
 
When n is odd, an = 0
2 2 8 2
and a2 = ( 2 cos π − 1 − cos 2π ) = ( −2 − 1 − 1) =− =− ,
π (2) 2 4π 4π π

2 2
=
a4 ( 2 cos 2π − 1 − cos=
4π ) ( 2 − 1=
− 1) 0 ,
π (4) 2 16π

2 2 8 2
a6 = ( 2 cos 3π − 1 − cos 6π ) = ( −2 − 1 − 1) =− =− ,
π (6) 2 36π 36π (3) 2 π

a8 = 0 ,

2 2 8 2
a10 = ( 2 cos 5π − 1 − cos10π ) = ( −2 − 1 − 1) =− =− , and so on
π (10) 2 100π 100π (5) 2 π


π 2 2 2
Thus, a0 + ∑ an cos nx =
f ( x) = − cos 2 x − cos 6 x − cos10 x + ...
n =1 4 π (3) 2 π (5) 2 π

π 2 cos 6 x cos10 x 
i.e. f ( x) =−  cos 2 x + + + ... 
4 π 32 5 2

1537 © 2014, John Bird